2016
DOI: 10.1038/srep25770
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing attempted and completed suicide in postnatal women: A population-based study in Taiwan

Abstract: The aims of study were to investigate risk factors associated with attempted and completed suicide. This nested case–control study was conducted using the medical and death data of nearly all pregnant women for the period 2002–2012 in Taiwan. A total of 139 cases of attempted suicide and 95 cases of completed suicide were identified; for each case, 10 controls were randomly selected and matched to the cases according to age and year of delivery. A conditional logistic regression model was used. The mean attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 54 publications
3
33
1
Order By: Relevance
“…The women who experienced a termination of pregnancy were more likely to share the same risk factors for suicide (such as younger age, being unmarried and still receiving education) and might experience more guilt resulting from termination of pregnancy. The results emphasise that women who completed suicide were distinct from women who attempted suicide …”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The women who experienced a termination of pregnancy were more likely to share the same risk factors for suicide (such as younger age, being unmarried and still receiving education) and might experience more guilt resulting from termination of pregnancy. The results emphasise that women who completed suicide were distinct from women who attempted suicide …”
Section: Discussionmentioning
confidence: 89%
“…Although suicidal behaviour ranges from suicidal ideation and attempted suicide to completed suicide, our examination focused more on the severe forms of attempted and completed suicide. Previously, we examined women who experienced a live birth and reported that those who were unmarried and had postpartum depressive disorder showed an increased risk of suicide within 1 year postnatally . In the current study, we further focused on women with fetal loss and investigated the risks of attempted and completed suicide in women who had experienced a stillbirth, miscarriage, or termination of pregnancy within 1 year after their fetal loss and compared the risks with those in women who had experienced a live birth.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, a logarithmic progression could help reconcile how young people can attempt and die by suicide at such high rates with relatively low PPEs (Berman, ; Cohen‐Sandler, Berman, & King, ). In addition, it could help explain how other populations with relatively low PPEs (e.g., first‐time pregnant mothers) are also able to attempt or die by suicide (Girardi et al., ; Weng, Chang, Yeh, Wang, & Chen, ). Lastly, it could possibly indicate whether there are stages of human development when a person is more vulnerable to rapidly developing ACS than at other times in their life.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal depression (PND) is a common maternal mental health problem which occurs worldwide at a prevalence ranging from 4.0% to 63.9% (Siti et al 2018). Recent studies have shown that PND not only causes an increased risk of suicide among the postnatal women (Weng et al 2016) but also contributes to the behavioural problems and negative emotions in the children (Netsi et al 2017;Prenoveau et al 2017). Despite the various negative consequences associated with PND, there is still a lack of effective measures taken to prevent PND.…”
Section: Introductionmentioning
confidence: 99%